Dating Violance Pada Perempuan (Studi Pada Empat Perempuan Korban Kekerasan Dalam Hubungan Pacaran Di Universitas X) - Asnia Mayasari; Kasmanto Rinaldi (UIR PRESS, 2017)
This research is generally intended to provide an overview of how the causesand forms of violence experienced by women in relationships with their partners, orthe so-called courtship. In this study using qualitative research methods. This studyshows that the causes of violence that occur in women due to the existence ofpatriarchal culture that developed in the community. In the relationship of courtshiprelationship that occurs there is a tendency that courtship is considered as a form ofownership of which arises instinct to regulate and master. So that the forms ofviolence that appear in this relation identify that women are as parties in the masterby his partner. Beatings, threats, restraints, are the means used by their malepartners in order to organize and master them. While it is recognized that women'seconomic dependency is fulfilled by their partners, the resulting form of violenceidentifies that it makes women weaker and has no strong bargaining position inrelationships. Until the form of violence that resulted in women being thedisadvantaged. This is one way to dominate a woman, the conscious and unconsciousactors force others to do what they want by playing with the fear, feelings of guilt orpity of others in order to exercise their dominance over women.